2022
DOI: 10.1590/1983-1447.2022.20200400.en
|View full text |Cite
|
Sign up to set email alerts
|

Cross-mapping of nursing diagnoses and interventions in decompensated heart failure

Abstract: Objective To map the terms recorded in medical records of patients with decompensated heart failure for nursing diagnoses and interventions from the NANDA International and Nursing Interventions Classification. Method This is an exploratory and descriptive research, carried out by a cross-mapping study. Data were collected from 107 medical records of a Hospital Institute in the city of Rio de Janeiro/Brazil, in a period between October 2017 to February 2019. The diagnoses and interventions mapped were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(27 reference statements)
0
4
0
3
Order By: Relevance
“…The official discussion of advanced nursing practice has gained prominence in the last decade, especially through debates in professional nursing councils. Although this practice is not yet a common reality in hospital units in the country, it is highly desirable, especially considering that hospitalized patients with decompensated HF require special care guided by clinical judgment and precise decision-making (23) . APN is emerging as an area of practice in which the nurse plays a central role in the provision and coordination of specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…The official discussion of advanced nursing practice has gained prominence in the last decade, especially through debates in professional nursing councils. Although this practice is not yet a common reality in hospital units in the country, it is highly desirable, especially considering that hospitalized patients with decompensated HF require special care guided by clinical judgment and precise decision-making (23) . APN is emerging as an area of practice in which the nurse plays a central role in the provision and coordination of specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…DCO was considered the priority diagnosis in several studies ( 30 - 32 ) . Other international ( 21 , 23 , 28 ) and national studies have identified DCO as one of the most prevalent diagnoses in people hospitalized with HF ( 20 , 27 , 29 , 35 , 42 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research carried out through cross-mapping, using 115 medical records of people with decompensated HF in a hospital specializing in cardiology, mapped DCO along with other diagnoses and NIC NI, such as monitoring vital signs, water monitoring and positioning, among the most prevalent ( 42 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations